Enterococcus faecalis capsular polysaccharide and mechanisms of host innate immune evasion - Thurlow, Lance R.; Thomas, Vinai Chittezham; Fleming, Sherry D.; Hancock, Lynn E. (My University, 2013)
It has become increasingly difficult to treat infections caused by Enterococcus faecalis due to the high levels of intrinsic and acquired antibiotic resistances. However, few studies have explored the mechanisms that E. faecalis employs to circumvent the host innate immune response and establish infection. Capsule polysaccharides are important virulence factors that are associated with innate immune evasion. We demonstrate that capsule producing E. faecalis strains of either serotype C or D are more resistant to complement-mediated opsonophagocytosis compared to un-encapsulated strains using cultured macrophages (RAW 264.7). We show that differences in opsonophagocytosis are not due to variation in C3 deposition, but due to the ability of capsule to mask bound C3 from detection on the surface of E. faecalis. Similarly, E. faecalis capsule masks detection of lipoteichoic acid which correlates with decreased TNF-α production by cultured macrophages in the presence of encapsulated strains compared to unencapsulated strains. Our studies confirm the important role of the capsule as a virulence factor of E. faecalis, and provide several mechanisms by which the presence of the capsule influences evasion of the innate immune response, and suggest that the capsule could be a potential target for developing alternative therapies to treat E. faecalis infections.
Enterococcus faecalis capsular polysaccharide serotypes C and D and their contributions to host innate immune evasion
Keywords: Enterococcus faecalis; Capsular polysaccharide; Innate immunity